Strategy for Enhancing Community Economy Through Optimization of Tourism Areas (A Study on Rawa Pening Lakes in Central Java Province - Indonesia) - Purwanto Purwanto; Retnowati Retnowati; Hari Suryanto (AIBPM Publisher, 2020)
This study aims to determine the contribution of economic value to the community and restore the natural function of the lake and maintain biodiversity. The qualitative description method is applied through journal reviews, documentation and field observations. The results of the study indicate that the joint commitment of all stakeholders and the community to be able to benefit optimally through scientific, social, political, ecological and economic approaches is necessary. Utilization of large eceng gondok helps reduce growth and bring benefits that can be used to meet maintenance needs. An environmentally sound development policy as a manifestation of sustainable tourism can be pursued through the implementation of a strategic plan, the Lake Ecosystem Rescue Movement, primary and tertiary activities.